BATIK GEBLEK RENTENG KULON PROGO : - aditya, rahadiyand (KOMUNITAS, 2019)
Intellectual Property Rights is a wealth of all the products of the production of intelligence, such as technology, knowledge, art, literature, compositions of songs, written works, caricatures, etc. that are useful for humans. IPR management can have both positive and negative consequences. Therefore, researchers will see the results of community empowerment strategies through the management of intellectual property rights for local batik products together in Kulon Progo. Informants used qualitative research with informants using snowballs. Data collection techniques are done using observation, interviews and documentation. Interviews were conducted with Bappeda and the Kulon Progo Regency industry, trade and ESDM department and the batik craft community in Kulon Progo. The Geblek renteng batik motif is a typical batik motif from Kulon Progo. Secondly, only the Kulon Progo community is permitted to produce joint-style geblek batik motifs. Third, there may not be artisans using batik stamps or printing in the making of geblek renteng batik motifs, fourth, providing training and capital assistance for batik craftsmen in the Kulon Progo region.